2007
DOI: 10.1523/jneurosci.0793-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rho via Arg and p190RhoGAP in the Postnatal Mouse Hippocampus Regulates Dendritic Spine Maturation, Synapse and Dendrite Stability, and Behavior

Abstract: The RhoA (Rho) GTPase is a master regulator of dendrite morphogenesis. Rho activation in developing neurons slows dendrite branch dynamics, yielding smaller, less branched dendrite arbors. Constitutive activation of Rho in mature neurons causes dendritic spine loss and dendritic regression, indicating that Rho can affect dendritic structure and function even after dendrites have developed. However, it is unclear whether and how endogenous Rho modulates dendrite and synapse morphology after dendrite arbor devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
164
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(184 citation statements)
references
References 57 publications
19
164
1
Order By: Relevance
“…The same phenotype has been observed in adolescent rodents tested before or during the period when the dendritic stabilizing effects of Arg are first detectable (10,23). To evaluate the degree to which Arg deficiency recapitulates the adolescent response to cocaine, we tested locomotor activity after repeated cocaine injection in P42 (peri-adolescent) and P180 (adult) mice.…”
Section: D2 Expression and Response Inhibitionmentioning
confidence: 68%
See 1 more Smart Citation
“…The same phenotype has been observed in adolescent rodents tested before or during the period when the dendritic stabilizing effects of Arg are first detectable (10,23). To evaluate the degree to which Arg deficiency recapitulates the adolescent response to cocaine, we tested locomotor activity after repeated cocaine injection in P42 (peri-adolescent) and P180 (adult) mice.…”
Section: D2 Expression and Response Inhibitionmentioning
confidence: 68%
“…Recent studies have identified a Rho inhibitory pathway involving integrin adhesion receptors, the Abl family tyrosine kinase, Arg, and the Rho inhibitor, p190RhoGAP, that acts in dendritic spines of late adolescent mice to maintain synapses and promote dendrite stability during maturation into adulthood. Cortical axons, dendrites, and synapses develop normally in Arg-deficient (arg Ϫ/Ϫ ) mice; but dendrites destabilize with age, leading to significant atrophy by 6 weeks (10,11), corresponding to adolescence in humans (12).…”
mentioning
confidence: 99%
“…For example, Arg is present at 0.4 -0.6 M in dendritic spines, and cortactin concentrations may be as high as 4 M within breast cancer cell invadopodia (12,17,41). Dendritic spines in Arg-deficient neurons exhibit a loss of cortactin, reduced actin content, morphological changes, and loss of stability both in culture and in vivo (7,32). The cooperative binding of Arg and cortactin to actin filaments that we have described may help to concentrate Arg and cortactin binding to individual subsets of actin filaments (17)(18)(19) at levels sufficient to influence filament stability, branching, and severing in key subcellular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Arg and cortactin act together to mediate the formation, function, and stability of breast cancer cell invadopodia, fibroblast membrane ruffles, and cell edge protrusions and neuronal dendritic spines (8,16,32,42), processes that depend on actin filament networks. We present multiple mechanisms by which Arg stabilizes filaments in a cooperative manner with its substrate, cortactin, and promotes actin nucleation through increased branching and severing.…”
Section: Discussionmentioning
confidence: 99%
“…Images were taken on a Joel 1220 TEM. PSD area was analyzed using ImageJ as previously described (21,37). Synaptic counts were taken at 2000 times magnification and clearly definable PSDs with presynaptic vesicles were counted as synapses.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%